2019
DOI: 10.1523/jneurosci.0330-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Mnemonic Introspection in Macaques Is Dependent on Superior Dorsolateral Prefrontal Cortex But Not Orbitofrontal Cortex

Abstract: The human PFC has been associated more with meta-perceptual as opposed to meta-memory decisions from correlational neuroimaging investigations. Recently, metacognitive abilities have also been shown to be causally dependent upon anterior and dorsal PFC in nonhuman primate lesion studies. Two studies, using postdecision wagering paradigms and reversible inactivation, challenged this meta-perceptual versus meta-memory notion and showed that dorsal and anterior prefrontal areas are associated with metamemory for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…Additionally, it also lies within the frontal lobe, which is not mixed by the temporal fibres in the Arcuate Fasciculus (Wakana, 2007) and is indicative of the DLPFC -IPL communication (Yeatman et al, 2012). On one end, the right DLPFC is involved in both perceptual and mnemonic metacognition in both humans and monkeys, and suggested as reading out information related to primary decision-making and computing metacognitive judgements (Fleming and Dolan, 2012;Kwok et al, 2019;Morales et al, 2018;Shekhar and Rahnev, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it also lies within the frontal lobe, which is not mixed by the temporal fibres in the Arcuate Fasciculus (Wakana, 2007) and is indicative of the DLPFC -IPL communication (Yeatman et al, 2012). On one end, the right DLPFC is involved in both perceptual and mnemonic metacognition in both humans and monkeys, and suggested as reading out information related to primary decision-making and computing metacognitive judgements (Fleming and Dolan, 2012;Kwok et al, 2019;Morales et al, 2018;Shekhar and Rahnev, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As cognitive processes are implemented in the brain, an interesting and important question is whether the neural circuit supporting metacognition is the same or distinct across different cognitive domains.A large body of fMRI work have increasingly demonstrated a nuanced picture for this domaingenerality issue of metacognition. For example, the dorsolateral prefrontal cortex (DLPFC) might be involved in reading out the information of primary decision-making and using it for computing both perceptual and mnemonic metacognitive judgements (Chua and Ahmed, 2016;Fleming and Dolan, 2012;Kwok et al, 2019;Rounis et al, 2010). Morales et al (2018) reported that the dorsal anterior cingulate cortex (dACC) was active during metacognitive evaluation in both memory and perception tasks but also found the activation patterns decoded from a perception task in the posterior medial frontal cortex and ventral medial prefrontal cortex could predict metacognitive judgements in a memory task.…”
mentioning
confidence: 99%
“…We hypothesize that perceptual and memory confidence are integrated in decision-making, which optimally depends on evidence from varied sources, on long timescales. Prior to this step, different forms of memory confidence may be computed differently, by different circuits 35 .…”
Section: A Framework For Understanding a Memory Confidence Computationmentioning
confidence: 99%
“…While there is evidence that humans 32 and primates 12,[33][34][35] compute memory confidence, studies have focused exclusively on visual recognition memory [33][34][35][36] , which can be solved by familiarity rather than true episode recollection 37 . Thus, whether these findings generalize to episodic memories is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Lesions to anterior prefrontal cortex impair perceptual metacognitive accuracy while sparing memory metacognitive accuracy [7][8]. Macaque monkey's metacognitive capability of introspecting its own memory success is causally dependent on intact superior dorsolateral prefrontal cortices but not the orbitofrontal cortices [9]. Studies in the past have indicated that variation in memory metacognitive efficiency was correlated with the volume of the precuneus [10].…”
Section: Introductionmentioning
confidence: 99%